The Development of Qur’anic Thematic Exegesis in Indonesia: Historical Landscape and Shifts of Authority - Lilik Ummi Kaltsum; Ahmad Syaifuddin Amin (UIN Sunan Kalijaga Yogyakarta, 2024)
Recognizing that thematic Qur'anic interpretation has become the most prominent method in the modern era, this study aims to track its evolution in Indonesia. Despite its popularity in academic contexts, there remains a critical gap in examining its application outside of universities. This study focuses on the shifts in interpretative authority and methodology in thematic Qur'anic exegesis across different sectors, including the state, Islamic boarding schools, universities, and individuals. Using a critical analysis method, the study uncovers several key findings. Firstly, there has been an authoritative shift, where Qur'anic commentators in Indonesia are not limited to traditional mufassir but now include scholars from non-religious fields. Secondly, methodological shifts are evident in several aspects: the editorial framing of interpretations, the reduction in the selection of Qur'anic verses used as primary research data, and the emergence of distinct interpretative tendencies. Additionally, there has been a paradigm shift in the relationship between Qur'anic text and social reality, where one approach begins with the Qur'an and leads to an idealistic-normative interpretation, while another starts from social reality and results in an applicative-solutive interpretation. This research fills a crucial academic gap by highlighting the broader changes in thematic exegesis, offering insights into its evolving methodologies and its relevance in addressing contemporary social realities in Indonesia.